MEMBENTUK MASYARAKAT WIRAUSAHA MANDIRI DAN BERJIWA MODERASI BERAGAMA DI DESA SEI MERAH KECAMATAN TANJUNG MORAWA - Muhammad Rizki Fadillah; Sity Hasyanah Sitompul; Sukma Aulia Munthe; Raisa Nur Salum; Nurul Hasanah; Annisa Dwi Syahputri; Maryam Batubara (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
Forming an independent society based on entrepreneurship learning to foster household socioeconomic awareness is a very important thing during the current COVID-19 pandemic. This activity is a Real Work Lecture for North Sumatra State Islamic University Students. This activity is carried out to empower housewives to become independent entrepreneurs and have a spirit of religious moderation in Sei Merah Village. In this case, housewives who take part in the Knitting Art Training held by KKN-130 students are expected to be able to assist household heads in meeting their primary, secondary, and tertiary needs. The products resulting from the knitting art training are in the form of connectors (mask connectors), key chains, and hijab brooches. Not only independent entrepreneurship, the residents of Sei Merah Village also have a good spirit of religious tolerance, religious moderation is needed so that our religious perspective is moderate, not exaggerating, not exceeding limits, and not extrem.